Knock, knock! - Susan, Iulia-Francesca (Satura, 2024)
"Knock, knock!" is a short story that delves into the life of Violet Emaline, a young woman grappling with her painful past and strained family relationships. Haunted by memories of her abusive father and the emotional scars left by her mother, Vio isolates herself, unable to let anyone in. Her new apartment, with its broken mirror, symbolizes her fragmented identity. Despite her mother's attempts to connect, Vio remains distant, burdened by unspoken truths and a name that holds painful associations. A turning point comes when a gentle, familiar voice at her door offers a promise of safety and love, prompting Vio to take a tentative step towards healing and acceptance. Through vivid imagery and emotional depth, the story explores themes of trauma, resilience, and the quest for a true home.